Pemanfaatan Perpustakaan Institut Francais Indonesie (Mediatek IFI) Jakarta sebagai Media Diplomasi Budaya - Ismi, Laura; Irawati, Indira (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2025)
Mediatek IFI Jakarta, as part of the Institut Français Indonésie (IFI), plays a vital role in supporting France’s cultural diplomacy in Indonesia. The library functions not only as a center for information access but also as a cultural space that facilitates language learning, exchange of ideas, and appreciation of French culture. This study aims to identify how Mediatek IFI Jakarta is utilized to strengthen France’s cultural diplomacy and foster intercultural understanding between France and Indonesia. A descriptive qualitative was employed in this research. Data were collected through interviews with two librarians and a pedagogical cooperation coordinator at IFI Jakarta. The analysis draws on Mariano’s concept of library diplomacy which made up of three dimensions: libraries in diplomacy, diplomacy for libraries, and libraries for diplomacy. The findings indicate that Mediatek IFI Jakarta supports French cultural diplomacy by shaping the library as an inclusive third place, leveraging their game collections, and designing cultural programs with the aspects of gamification to expand access and build mutual understanding of French and Indonesian cultures.